Separator for lithium secondary battery and method for producing same
Patent Information
- Application Number
- JP2022572420
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2021-10-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-10-15
AI Technical Summary
【0023】 本発明の一態様によれば、無機物粒子を従来に対比して高い含量で維持し、フッ素系バインダー高分子とポリビニルアセテートバインダー高分子とを同時に使用した分離膜を提供することができる。これにより、電極との接着力(Lami strength)が向上し、分離膜の耐熱性を増加させることができる。また、多孔性高分子基材内の気孔閉塞を減少できるため、分離膜内の抵抗を減少させることができる。
Smart Images

Figure 0007634565000005 
Figure 0007634565000006 
Figure 0007634565000007
Abstract
Description
[Technical field]
[0001] The present invention claims priority to Korean Patent Application No. 10-2020-0134283, filed on October 16, 2020.
[0002] The present invention relates to a separator applicable to electrochemical devices such as lithium secondary batteries, and a method for manufacturing the same. [Background technology]
[0003] In recent years, interest in energy storage technology has been increasing. As the fields of application expand to include mobile phones, camcorders, and laptops, as well as the energy of electric vehicles, efforts in the research and development of electrochemical elements have been increasingly realized. Electrochemical elements are the field that has attracted the most attention from this perspective, and in particular, the development of rechargeable secondary batteries has attracted attention. In recent years, in the development of such batteries, research and development related to the design of new electrodes and batteries has been conducted in order to improve the capacity density and specific energy.
[0004] Among the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of high operating voltage and significantly higher energy density compared to conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries.
[0005] Electrochemical devices such as lithium secondary batteries are produced by many manufacturers, but their safety characteristics vary from one another. It is very important to evaluate and ensure the safety of such electrochemical devices. For example, a separator prevents short circuits between the positive and negative electrodes and provides a path for lithium ions to move. Therefore, the separator is an important factor that affects the safety and output characteristics of a battery. In particular, polyolefin-based porous polymer substrates that are commonly used as separators for electrochemical devices have a problem of causing short circuits between the positive and negative electrodes by exhibiting severe thermal shrinkage behavior at temperatures above 100°C due to material properties and manufacturing process properties including stretching.
[0006] In order to solve the safety problem of such electrochemical devices, a separator has been proposed in which a porous coating layer is formed by coating at least one surface of a porous polymer substrate having a large number of pores with a mixture of an excess amount of inorganic particles and a binder polymer.
[0007] The porous coating layer forms pores mainly through humidification phase separation or immersion phase separation. Among these, the porous coating layer formed by humidification phase separation is superior to the immersion phase separation in terms of thermal shrinkage rate, but there is a problem that the binder polymer contained in the slurry during the formation of the porous coating layer clogs the pores of the porous polymer substrate.
[0008] Meanwhile, immersion phase separation has the advantage that the resistance before and after coating of the porous polymer substrate is lower than that of conventional humid phase separation because the coating layer solidifies at the same time as the slurry is applied to the substrate. In other words, the pores of the porous polymer substrate are not blocked by the binder polymer. However, the porous coating layer produced by immersion phase separation has problems such as inferior thermal shrinkage, especially at high temperatures, and low adhesion strength between the separator and the electrode, compared to humid phase separation. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention provides a separator that utilizes the advantages of immersion phase separation to reduce pore blockage in a porous polymer substrate, improves adhesion to an electrode, and enhances heat shrinkage, and a method for manufacturing the same. [Means for solving the problem]
[0010] An aspect of the present invention provides a separator for a lithium secondary battery according to the following embodiment.
[0011] The first embodiment is A porous polymer substrate; a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles, a fluorine-based binder polymer, and a polyvinyl acetate (PVAc) binder polymer; the porous coating layer has a structure in which the inorganic particles are dispersed in a matrix formed by the fluorine-based binder polymer and the polyvinyl acetate binder polymer, and the fluorine-based binder polymer, the polyvinyl acetate binder polymer, and the inorganic particles are uniformly distributed in a thickness direction of the porous coating layer; The content of the inorganic particles is 70 parts by weight or more based on 100 parts by weight of the porous coating layer, The content of the polyvinyl acetate binder polymer is less than 80 parts by weight based on 100 parts by weight of the total content of the binder polymer.
[0012] The second embodiment is A porous polymer substrate; a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles, a fluorine-based binder polymer, and a polyvinyl acetate (PVAc) binder polymer; the pores in the porous coating layer are formed by material exchange between a solvent and a non-solvent for the binder polymer; The content of the inorganic particles is 70 parts by weight or more based on 100 parts by weight of the porous coating layer, The content of the polyvinyl acetate binder polymer is less than 80 parts by weight based on 100 parts by weight of the total content of the binder polymer.
[0013] According to a third embodiment, in the first or second embodiment, The content of the polyvinyl acetate binder polymer may be 5 to 75 parts by weight based on 100 parts by weight of the binder polymer.
[0014] According to the fourth embodiment, in the second or third embodiment, The solvent may include one or more selected from N-methyl-2-pyrrolidone, dimethylacetamide, and dimethylformamide.
[0015] According to the fifth embodiment, in any one of the second to fourth embodiments, The non-solvent may be water.
[0016] According to the sixth embodiment, in any one of the first to fifth embodiments, The fluorine-based binder polymer may have a weight average molecular weight of 100,000 to 1,500,000.
[0017] According to the seventh embodiment, in any one of the first to sixth embodiments, The weight average molecular weight of the polyvinyl acetate binder polymer may be 100,000 to 1,000,000.
[0018] According to the eighth embodiment, in any one of the first to seventh embodiments, The adhesive strength (Lami strength) between the separator and the electrode may be 60 gf / 25 mm or more.
[0019] According to the ninth embodiment, in any one of the first to eighth embodiments, The separator may have a heat shrinkage of 10% or less in at least one of the machine direction and the transverse direction, measured after heating at 150° C. for 30 minutes.
[0020] Another aspect of the present invention provides an electrochemical device according to the following embodiment.
[0021] The tenth embodiment is The battery includes a positive electrode, a negative electrode, and a separator interposed between the negative electrode and the positive electrode, The separator may be any of the separators according to any of the above-described embodiments.
[0022] According to the eleventh embodiment, in the tenth embodiment, The electrochemical device may be a lithium secondary battery. Effect of the Invention
[0023] According to one aspect of the present invention, a separator can be provided that maintains a higher content of inorganic particles than conventional ones and simultaneously uses a fluorine-based binder polymer and a polyvinyl acetate binder polymer. This improves the adhesion strength with the electrode and increases the heat resistance of the separator. In addition, the resistance in the separator can be reduced by reducing the clogging of pores in the porous polymer substrate.
[0024] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a schematic diagram of a separation membrane prepared by humid phase separation according to a comparative example of the present invention. [Diagram 2] 1 is a SEM photograph of a separation membrane prepared by humid phase separation according to a comparative example of the present invention. [Diagram 3] 1 is a schematic diagram of a separation membrane manufactured by immersion phase separation according to an embodiment of the present invention. [Figure 4] 1 is a SEM image of a separator prepared by immersion phase separation according to an embodiment of the present invention. [Diagram 5] 1 is a SEM photograph showing the surface of the separation membrane according to Comparative Example A. [Figure 6] 1 is a SEM photograph showing the surface of the separation membrane according to Example B. [Figure 7] 1 is a SEM photograph showing the surface of the separation membrane according to Example C. [Figure 8] 1 is a SEM photograph showing the surface of the separation membrane according to Comparative Example B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0027] Throughout this specification, when a certain portion is referred to as being "connected" to another portion, this includes not only a "direct connection" but also an "indirect connection" via another member. Furthermore, the connection includes not only a physical connection but also an electrochemical connection.
[0028] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.
[0029] Additionally, as used in this specification, "comprise" or "comprising" specifies the presence of stated features, numbers, steps, operations, members, elements and / or groups, but does not exclude the presence or addition of one or more other features, numbers, operations, members, elements and / or groups.
[0030] In addition, the terms "about," "substantially," and the like, used throughout this specification, when given the manufacturing and material tolerances inherent in the stated meaning, are used to mean a numerical value or close to that numerical value, and are used to prevent unscrupulous infringers from unfairly taking advantage of disclosures in which precise or absolute numerical values are stated to aid in the understanding of this application.
[0031] Throughout this specification, the term "combinations thereof" contained in a Markush form expression means a mixture or combination of one or more selected from the group of components set forth in the Markush form expression, and is meant to include one or more selected from the group of components set forth above.
[0032] Throughout this specification, the phrase "A and / or B" means "A, B, or all of these."
[0033] In lithium secondary batteries, a separator is interposed between a positive electrode and a negative electrode to prevent physical contact and electrical short circuit between the positive electrode and the negative electrode. Such a separator is mainly made of a polyolefin-based porous polymer substrate, and a separator having a porous coating layer containing inorganic particles and a binder polymer on at least one surface of the porous polymer substrate is mainly used to prevent thermal shrinkage of the porous polymer substrate and to increase adhesion to the electrode.
[0034] In this case, the porous coating layer can form a pore structure by humidification phase separation or immersion phase separation. In humidification phase separation, a slurry for forming a porous coating layer is applied onto a porous polymer substrate, and then dried under humid conditions. In this case, the binder polymer in the slurry moves to the surface of the porous coating layer together with the solvent to enhance adhesion with the electrode, and pores are formed at the locations where the solvent is evaporated. Thus, in humidification phase separation, the porous coating layer can be broadly divided into a dispersion layer in which inorganic particles and binder polymer are uniformly dispersed, and an adhesion layer in which binder polymer is mainly distributed.
[0035] Meanwhile, immersion phase separation is a method in which a slurry for forming a porous coating layer is applied onto a porous polymer substrate, and the substrate is then immersed in a coagulation bath containing a non-solvent to form pores by material exchange between the solvent in the slurry and the non-solvent in the coagulation bath. In immersion phase separation, the solvent is not dried and volatilized, so unlike humidification phase separation, a so-called adhesive layer is not formed on the surface of the porous coating layer. In other words, immersion phase separation is a structure in which inorganic particles are uniformly dispersed in a binder polymer matrix.
[0036] The porous coating layer produced by immersion phase separation has a lower adhesive strength with the electrode than the porous coating layer produced by humidification phase separation because of the absence of an adhesive layer, and has a lower thermal shrinkage rate because of a lower content of inorganic particles. If the content of inorganic particles is increased to improve the thermal shrinkage rate, the adhesive strength with the electrode is further reduced.
[0037] Accordingly, the present invention aims to provide a separator manufactured by immersion phase separation, which has an improved thermal shrinkage rate and increased adhesive strength with an electrode.
[0038] According to one aspect of the present invention, a separator for a lithium secondary battery includes a porous polymer substrate, a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles, a fluorine-based binder polymer, and a polyvinyl acetate (PVAc) binder polymer; the porous coating layer has a structure in which the inorganic particles are dispersed in a matrix formed by the fluorine-based binder polymer and the polyvinyl acetate binder polymer, and the fluorine-based binder polymer, the polyvinyl acetate binder polymer, and the inorganic particles are uniformly distributed in a thickness direction of the porous coating layer; The content of the inorganic particles is 70 parts by weight or more based on 100 parts by weight of the porous coating layer, The content of the polyvinyl acetate binder polymer is less than 80 parts by weight based on 100 parts by weight of the total content of the binder polymer.
[0039] In the separator for lithium secondary batteries according to an embodiment of the present invention, a porous coating layer is formed by a so-called immersion phase separation method. That is, the binder polymer and inorganic particles are uniformly distributed in the porous coating layer. In other words, a separate adhesive layer is not included. In the separator formed by the immersion phase separation method, the coating layer is solidified at the same time as the slurry is applied, so that the phenomenon that the pores in the porous polymer substrate are blocked by the binder polymer, which is a problem in the conventional humid phase separation, can be reduced. In addition, since the pores in the separator according to an embodiment of the present invention are formed by an exchange reaction between a solvent and a non-solvent, the pores are less complicated than those in the porous coating layer formed by humid phase separation, and the resistance of the separator is relatively low.
[0040] 1 and 2 are schematic diagrams and SEM images of a separation membrane prepared by humid phase separation according to a comparative example of the present invention. As can be seen from FIG. 1, in the separation membrane prepared by the conventional humid phase separation, the binder polymer 22 is mainly located on the surface of the porous coating layer 20.
[0041] Meanwhile, FIG. 3 and FIG. 4 are a schematic diagram and a SEM image of a separator prepared by immersion phase separation according to an embodiment of the present invention.
[0042] As can be seen from FIG. 3, in the separation membrane according to one embodiment of the present invention, the binder polymer 42 forms a matrix structure, and the inorganic particles 41 are dispersed within the matrix.
[0043] In the separator according to one embodiment of the present invention, the content of inorganic particles in the porous coating layer is 70 parts by weight or more based on 100 parts by weight of the porous coating layer.
[0044] According to the conventional immersion phase separation method, the content of inorganic particles is about 60 parts by weight based on 100 parts by weight of the porous coating layer. In other words, according to the conventional immersion phase separation method, the content of binder polymer in the porous coating layer is about 40 parts by weight based on 100 parts by weight of the porous coating layer. This is a value that is about 15 to 20% lower in inorganic particle content than humid phase separation. According to the immersion phase separation method, since a separate adhesive layer is not formed on the surface of the porous coating layer due to structural limitations, the content of binder polymer is relatively increased to increase the adhesive strength with the electrode. However, in exchange, the content of inorganic particles is reduced, and the thermal shrinkage rate is relatively inferior to that of the conventional humid phase separation.
[0045] The present inventors attempted to improve the thermal shrinkage rate and increase the adhesive strength with the electrode by increasing the content of inorganic particles in the separator produced by immersion phase separation.
[0046] That is, according to one embodiment of the present invention, the content of the inorganic particles is 70 parts by weight or more, 71 parts by weight or more, 72 parts by weight or more, 73 parts by weight or more, 74 parts by weight or more, or 75 parts by weight or more, and 95 parts by weight or less, 90 parts by weight or less, or 85 parts by weight or less, based on 100 parts by weight of the porous coating layer. If the content of the inorganic particles is less than 70 parts by weight, the desired thermal shrinkage rate cannot be obtained in the present invention. If the content of the inorganic particles satisfies the above range, the desired thermal shrinkage rate can be obtained and at the same time, adhesion to the electrode can be secured.
[0047] In the present invention, the inorganic particles are not particularly limited as long as they are electrochemically stable. In other words, the inorganic particles usable in the present invention are those that are within the operating voltage range (e.g., Li / Li + There are no particular limitations as long as the oxidation and / or reduction reaction does not occur at a voltage of 0 to 5 V relative to the reference voltage. In particular, when inorganic particles having a high dielectric constant are used as the inorganic particles, the degree of dissociation of an electrolyte salt, for example, a lithium salt, in the liquid electrolyte can be increased, thereby improving the ionic conductivity of the electrolyte.
[0048] For the reasons described above, the inorganic particles can be inorganic particles having a relative permittivity constant of 5 or more, inorganic particles having lithium ion conductivity, or a mixture thereof.
[0049] The inorganic particles having a relative permittivity constant of 5 or more are Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3 (PZT, where 0 < x < 1), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, where 0 < x < 1, 0 < y < 1), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O3 - xPbTiO3 (PMN - PT, where 0 < x < 1), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC, and can be one or more mixtures selected from the group consisting of.
[0050] The inorganic particles having lithium ion conductivity are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2 - based glass (Lix Si y S z 、 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5-based glass (Li x P y S z 、 0 < x < 3, 0 < y < 3, 0 < z < 7), and may be one or more mixtures selected from the group consisting of.
[0051] The average particle size of the inorganic particles is not particularly limited, but for the formation of a porous coating layer with a uniform thickness and an appropriate porosity, it is preferably in the range of 0.001 to 10 μm, more preferably 10 nm to 2 μm, and even more preferably 50 nm to 1 μm.
[0052] Throughout this specification, the average particle size of the inorganic particles is D 50 particle size, and "D 50 particle size" means the particle size at the 50% point of the particle number cumulative distribution according to the particle size. The particle size can be measured using the laser diffraction method. Specifically, after dispersing the powder to be measured in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (for example, Microtrac S3500). When the particles pass through the laser beam, the difference in the diffraction pattern according to the particle size is measured to calculate the particle size distribution. By calculating the particle size at the point where the particle number cumulative distribution according to the particle size in the measuring device reaches 50%, D 50 particle size can be measured.
[0053] The porous coating layer contains a fluorine-based binder polymer and a polyvinyl acetate binder polymer.
[0054] The fluorine-based binder polymer has adhesive properties and provides the adhesive force between the porous polymer substrate and the porous coating layer or provides the adhesive force between the porous coating layer and the electrode. Also, it serves to fix the inorganic particles in the porous coating layer so that they do not detach.
[0055] In a specific embodiment of the present invention, the fluorine-based binder polymer may include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-tetrafluoroethylene copolymer, or two or more of them.
[0056] In a specific embodiment of the present invention, the weight average molecular weight of the fluorine-based binder polymer may be 100,000 or more, 200,000 or more, or 300,000 or more, and may be 1,500,000 or less, 1,000,000 or less, or 800,000 or less. For example, in order to ensure heat resistance and adhesiveness as well as processability, the weight average molecular weight may be 300,000 to 800,000.
[0057] In this case, the weight average molecular weight of the fluorine-based binder polymer can be measured using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies).
[0058] Specifically, the measurement can be performed under the following analytical conditions.
[0059] -Column: PL MiniMixed Bx2 -Solvent: DMF -Flow rate: 0.3ml / min -Sample concentration: 2.0mg / ml -Injection volume: 10μl -Column temperature: 40℃ -Detector: Agilent RI detector -Standard: Polystyrene (corrected by a cubic function) -Data processing: ChemStation
[0060] In a separator prepared by conventional immersion phase separation, when only a fluorine-based binder polymer is included in the porous coating layer, the adhesive strength with the electrode is insufficient. On the other hand, in one embodiment of the present invention, the adhesive strength between the separator and the electrode can be ensured by using the fluorine-based binder polymer and the polyvinyl acetate binder polymer simultaneously.
[0061] In the separator according to one embodiment of the present invention, the content of the polyvinyl acetate binder polymer is less than 80 parts by weight based on the total content of the binder polymer.
[0062] In a specific embodiment of the present invention, the content of the polyvinyl acetate binder polymer may be 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, and may be less than 80 parts by weight, 75 parts by weight or less, 70 parts by weight or less, 65 parts by weight or less, 60 parts by weight or less, 55 parts by weight or less, 50 parts by weight or less, 45 parts by weight or less, or 40 parts by weight or less, based on the total content of the binder polymer. Ventilation time The rate of increase in the temperature becomes large, which is not suitable for achieving the effects of the present invention.
[0063] In one embodiment of the present invention, the weight average molecular weight of the polyvinyl acetate binder polymer may be 100,000 or more, 200,000 or more, or 300,000 or more, and may be 1,000,000 or less, 900,000 or less, or 800,000 or less. For example, in order to ensure heat resistance and adhesiveness as well as processability, the weight average molecular weight may be 300,000 to 800,000.
[0064] At this time, the weight average molecular weight of the polyvinyl acetate binder polymer can be measured using gel permeation chromatography (GPC, PL GPC220, manufactured by Agilent Technologies).
[0065] Specifically, the measurement can be performed under the following analytical conditions.
[0066] -Column: PL MiniMixed Bx2 -Solvent: DMF -Flow rate: 0.3ml / min -Sample concentration: 2.0mg / ml -Injection volume: 10μl -Column temperature: 40℃ -Detector: Agilent RI detector -Standard: Polystyrene (corrected by a cubic function) -Data processing: ChemStation
[0067] In the separation membrane according to an embodiment of the present invention, the porous polymer substrate may be, specifically, a porous polymer film substrate or a porous polymer nonwoven fabric substrate.
[0068] The porous polymer film substrate may be a porous polymer film made of a polyolefin such as polyethylene or polypropylene, and such a polyolefin porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80 to 150°C.
[0069] In this case, the polyolefin porous polymer film may be formed by using a polyolefin polymer such as polyethylene (e.g., high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, etc., either alone or in combination of two or more of these.
[0070] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.
[0071] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, etc., either alone or in combination, in addition to the above-mentioned polyolefin-based polymers.
[0072] The thickness of the porous polymer substrate is not particularly limited, but is preferably 1 to 100 μm, more preferably 5 to 50 μm. The pore size and porosity of the porous polymer substrate are not particularly limited, but are preferably 0.01 to 50 μm and 20 to 75%, respectively.
[0073] The porosity and pore size of the porous polymer substrate can be measured by a BET 6-point method using a scanning electron microscope (SEM) image, a mercury porosimeter, a capillary flow porometer, or a porosimetry analyzer (Bell Japan, Belsorp-II mini) with nitrogen gas adsorption flow.
[0074] The thickness of the porous coating layer is not particularly limited, but is preferably 1 to 15 μm, more preferably 1.5 to 10 μm, based on the cross-sectional coating. The porosity of the porous coating layer is also not particularly limited, but is preferably 35 to 85%.
[0075] The porosity of the porous coating layer can be measured by scanning electron microscope (SEM) images, mercury porosimeter, capillary flow porometry, or nitrogen gas adsorption flow using a pore distribution measuring device (Bell Japan, Belsorp-II mini) using a BET 6-point method.
[0076] In the porous coating layer, inorganic particles are packed and in contact with each other and bound to each other by the binder polymer, forming interstitial volumes between the inorganic particles, and the interstitial volumes between the inorganic particles can become empty spaces to form pores.
[0077] That is, the binder polymer may attach the inorganic particles to each other so that they can maintain a state of being bound to each other, for example, the binder polymer may connect and fix the inorganic particles to each other. Also, the pores of the porous coating layer are pores formed when the interstitial volume between the inorganic particles becomes an empty space, and this may be a space limited by inorganic particles that are substantially in contact with each other in a packed structure of inorganic particles (closely packed or densely packed).
[0078] The components of the slurry for forming the porous coating layer may further include a dispersant and other additives in addition to the inorganic particles and the binder polymer described above.
[0079] The separator for a lithium secondary battery according to an embodiment of the present invention may have an adhesive strength (Lami strength) with an electrode of 60 gf / 25 mm or more.
[0080] The adhesive strength between the separator and the electrode can be determined as follows. First, the separator and the electrode are stacked and sandwiched between 100 μm PET films, and heated and pressed at 60° C. and 6.5 MPa for 1 second in a flat press to bond them together. This is attached to a slide glass using double-sided tape, and the end of the separator adhesive surface is separated and attached to the PET film and cross-section adhesive tape so that the longitudinal direction is connected. Then, the slide glass is attached to the lower holder of the UTM device, and the separator and the attached PET film are attached to the upper holder of the UTM device, and a force is applied at a measurement speed of 300 mm / min and 180° to measure and determine the force required to peel the electrode and the porous coating layer facing the electrode.
[0081] The separator for a lithium secondary battery according to an embodiment of the present invention may have a heat shrinkage rate of 10% or less in at least one of the machine direction and the transverse direction.
[0082] The heat shrinkage rate is a value measured after heating at 150° C. for 30 minutes.
[0083] The heat shrinkage rate is calculated by (initial length-length after heat shrinkage treatment at 150°C for 30 minutes) / (initial length)×100.
[0084] According to another aspect of the present invention, a method for producing a separator for a lithium secondary battery includes: (S1) preparing a slurry for forming a porous coating layer, the slurry including inorganic particles, a fluorine-based binder polymer, a polyvinyl acetate binder polymer, and a solvent for the fluorine-based binder polymer; (S2) applying the slurry for forming a porous coating layer to at least one surface of a porous polymer substrate; (S3) immersing the result of (S2) in an immersion bath containing a non-solvent for the fluorine-based binder polymer to form a porous coating layer; The content of the inorganic particles is 70 parts by weight or more based on 100 parts by weight of the porous coating layer.
[0085] First, (S1) a slurry for forming a porous coating layer is prepared, which contains inorganic particles, a fluorine-based binder polymer, a polyvinyl acetate binder polymer, and a solvent for the fluorine-based binder polymer.
[0086] For the inorganic particles, the fluorine-based binder polymer, and the polyvinyl acetate binder polymer, see the above.
[0087] At this time, the inorganic particles are dispersed in the solvent, and the fluorine-based binder polymer and the polyvinyl acetate binder polymer are dissolved in the solvent.
[0088] In the present invention, the solvent of the slurry for forming the porous coating layer is a solvent capable of dissolving the binder polymer, specifically, a solvent capable of dissolving 10 wt % or more of the binder polymer at 25°C.
[0089] In a specific embodiment of the present invention, the solvent may include one or more selected from N-methyl-2-pyrrolidone, dimethylacetamide, and dimethylformamide.
[0090] Next, the slurry for forming a porous coating layer is applied to at least one surface of a porous polymer substrate (S2).
[0091] The slurry may be applied by a coating method generally used in the technical field of the present invention, such as a Mayer bar, a die coater, a reverse roll coater, a gravure coater, etc. When the porous coating layer is formed on both sides of the porous polymer substrate, the coating liquid may be applied to each side, followed by solidification, washing with water, and drying, but from the viewpoint of productivity, it is preferable to simultaneously apply the coating liquid to both sides of the porous polymer substrate, followed by solidification, washing with water, and drying.
[0092] Thereafter, the resultant product of step (S2) is immersed in a coagulation liquid containing a non-solvent for the fluorine-based binder polymer (S3).
[0093] In the present invention, the non-solvent is one that can dissolve the fluorine-based binder polymer and the polyvinyl acetate binder polymer independently at less than 5 wt % at 25° C. In other words, it means a solvent that does not dissolve the binder polymer, and is not particularly limited as long as it is a liquid that is miscible with the solvent used to facilitate phase separation.
[0094] In a specific embodiment of the present invention, the non-solvent may include one or more selected from water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, and tripropylene glycol.
[0095] Meanwhile, in one embodiment of the present invention, the immersion time may be controlled to 30 to 100 seconds, or 40 to 90 seconds. When the immersion time satisfies this range, the problem of the coating layer being detached due to a decrease in adhesive strength between the porous polymer substrate and the porous coating layer caused by excessive phase separation can be easily prevented, and uniform pores in the thickness direction can be easily formed.
[0096] The step (S3) may be a process of phase-separating the slurry for forming a porous coating layer coated on the porous polymer substrate through material exchange between the solvent and the non-solvent.
[0097] After the step (S3), the method may include a step of drying the phase-separated slurry for forming the porous coating layer to form the porous coating layer.
[0098] The drying may be performed in a drying chamber, and the conditions of the drying chamber are not particularly limited depending on the application of the non-solvent.
[0099] An electrochemical device according to an aspect of the present invention includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the separator is the separator according to the embodiment of the present invention described above.
[0100] Such electrochemical devices include any device that performs an electrochemical reaction, and specifically include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices, etc. In particular, among the secondary batteries, lithium secondary batteries, including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries, are preferred.
[0101] The positive and negative electrodes to be used with the separator of the present invention are not particularly limited, and may be prepared by bonding the electrode active material to the electrode current collector by a conventional method known in the art. Among the electrode active materials, non-limiting examples of the positive electrode active material include conventional positive electrode active materials used in the positive electrode of conventional electrochemical devices, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide made by combining these materials. Non-limiting examples of the negative electrode active material include conventional negative electrode active materials used in the negative electrode of conventional electrochemical devices, and in particular, lithium adsorbent materials such as lithium metal or lithium alloy, carbon, petroleum coke, activated carbon, graphite, or other carbons are preferred. Non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.
[0102] The electrolyte used in the electrochemical element of the present invention is A + B - A salt with the structure: + Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 -or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof.
[0103] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired physical properties of the final product, i.e., before battery assembly or at the final stage of battery assembly.
[0104] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0105] [Experimental Example 1] Table 1 shows a comparison of separation membranes produced by humid phase separation and immersion phase separation.
[0106] Example I A slurry for forming a porous coating layer was prepared by dispersing Al2O3 (AES11, manufactured by Sumitomo) as inorganic particles in N-methyl-2-pyrrolidone as a solvent, and dissolving polyvinylidene fluoride-hexafluoropropylene (Solef 21510, manufactured by Solvay) as a fluorine-based binder polymer and polyvinyl acetate binder polymer (Sigma-Aldrich) in the solvent. At this time, the weight ratio of inorganic particles:fluorine-based binder polymer:polyvinyl acetate binder polymer was 70:25:5.
[0107] The prepared slurry for forming the porous coating layer was applied to one side of a 9 μm-thick polyethylene-based porous polymer substrate (WL11B, manufactured by Double Scope Co., Ltd., ventilation time 150 sec / 100 cc) using a doctor blade. The temperature of the slurry when applied was 15°C.
[0108] The resultant was then immersed in a coagulation solution containing water as a non-solvent, and then dried at 75° C. using an oven as a drying furnace to finally manufacture a separator for an electrochemical device. The results are shown in Table 1 below.
[0109] Comparative example I A binder polymer solution was prepared by adding polyvinylidene fluoride-hexafluoropropylene (Solef 21510, Solvay) as a fluorine-based binder polymer to acetone as a solvent and dissolving it at 50°C for about 4 hours. Al2O3 (AES11, Sumitomo) as inorganic particles was added to the prepared binder polymer solution, and the inorganic particles were crushed and dispersed using a ball mill method for 12 hours to prepare a slurry for forming a porous coating layer. At this time, the weight ratio of inorganic particles to fluorine-based binder polymer was 70:30.
[0110] The slurry for forming the porous coating layer was applied by dip coating at 23° C. and 40% relative humidity with a total loading of 13.5 g / m on both sides. 2 The result is shown in Table 1 below.
[0111] Comparative Example II A binder polymer solution was prepared by adding polyvinylidene fluoride-hexafluoropropylene (Solef 21510, Solvay) as a fluorine-based binder polymer and polyvinyl acetate binder polymer (Sigma-Aldrich) to acetone as a solvent and dissolving at 50°C for about 4 hours. Al2O3 (AES11, Sumitomo) as inorganic particles was added to the prepared binder polymer solution, and the inorganic particles were crushed and dispersed using a ball mill method for 12 hours to prepare a slurry for forming a porous coating layer. At this time, the weight ratio of inorganic particles: fluorine-based binder polymer: polyvinyl acetate binder polymer was 70: 25: 5.
[0112] The slurry for forming the porous coating layer was applied by dip coating at 23° C. and 40% relative humidity with a total loading of 13.5 g / m on both sides. 2 The result is shown in Table 1 below.
[0113] [Table 1]
[0114] From Table 1, it can be seen that the degree of pore blockage of the porous polymer substrate is reduced after removal of the coating layer and cleaning of the separator prepared in Example I. On the other hand, when the porous coating layer is formed by humid phase separation as in Comparative Examples I and II, the degree of blockage of the porous coating layer after coating increased by more than 100%. In addition, when the porous coating layer is formed by humid phase separation as in Comparative Example I, the degree of pore blockage after removal of the porous coating layer and cleaning was less than the results of Example I. 7.5 % increase. In Comparative Example II, when a porous coating layer was formed by humid phase separation using the same composition as in Example I, the degree of pore blockage after removal and cleaning of the porous coating layer was greater than that in Example I. 4It can be seen that the increase was %.
[0115] [Experimental Example 2] Table 2 shows a comparison between the separation membranes prepared by the conventional humid phase separation, the conventional immersion phase separation, and the separation membrane prepared according to one embodiment of the present invention.
[0116] Examples II to V A separator was manufactured in the same manner as in Example I, except that the composition of the slurry for forming the porous coating layer was controlled as shown in Table 2 below.
[0117] Comparative examples III~V A separator was manufactured in the same manner as in Example I, except that the composition of the slurry for forming the porous coating layer was controlled as shown in Table 2 below.
[0118] [Table 2]
[0119] Comparative Example I is a case where a separator was manufactured by conventional humid phase separation. As can be seen from Table 2, it is superior in terms of heat shrinkage rate compared to immersion phase separation. In addition, the adhesive strength with the electrode is also excellent at 90gf / 25mm. However, there is a problem that the degree of blockage of the porous polymer substrate is large at 1.15 Ohm, which is large, resulting in high resistance.
[0120] Comparative Examples III to V are separators manufactured by conventional immersion phase separation. In the conventional immersion phase separation method, the content of inorganic particles was 60 parts by weight based on 100 parts by weight of the porous coating layer. In the immersion phase separation method, a separate adhesive layer is not formed on the surface of the porous coating layer due to structural limitations, so the content of the binder polymer was relatively increased to increase the adhesive strength with the electrode. This can be seen from Table 2. Meanwhile, it can be seen that the heat shrinkage rate of Comparative Example III was 12 / 15, which is inferior to that of Comparative Example I, which is a separator by humid phase separation.
[0121] When the weight ratio of inorganic particles to binder polymer is 70:30 as in Comparative Example IV, it is confirmed that the adhesive strength and heat shrinkage rate are still inferior to the separation membrane by humid phase separation in Comparative Example I. In fact, the adhesive strength is significantly lower than in Comparative Example III, and no significant effect is obtained in terms of the heat shrinkage rate.
[0122] When the weight ratio of inorganic particles to binder polymer was 90:10 as in Comparative Example V, the thermal shrinkage rate was equal to or similar to that of Comparative Example I, but there was a problem of a significant decrease in adhesive strength with the electrode.
[0123] Meanwhile, looking at Examples I to V according to one embodiment of the present invention, as can be seen from Table 2, it can be seen that the degree of pore blocking of the porous polymer substrate is 1.0 Ohm or less, the thermal shrinkage rate is 10% or less in at least one of the transverse direction (TD) / machine direction (MD), and the adhesive strength with the electrode is 60 gf / 25 mm or more, thereby achieving the effects of the present invention.
[0124] [Experimental Example 3] Experimental Example 3 is a combination of a fluorine-based binder polymer and polyvinyl acetate The purpose of the experiment was to investigate the difference in adhesive strength depending on the content of inorganic particles.
[0125] Example A A slurry for forming a porous coating layer was prepared by dissolving polyvinylidene fluoride-hexafluoropropylene (Solef 21510, Solvay) as a fluorine-based binder polymer and polyvinyl acetate binder polymer (Sigma-Aldrich) in N-methyl-2-pyrrolidone as a solvent. acetate The weight ratio of the binder polymer was 95:5.
[0126] The prepared slurry for forming the porous coating layer was applied to one side of a 9 μm-thick polyethylene-based porous polymer substrate (WL11B, manufactured by Double Scope Co., Ltd., ventilation time 150 sec / 100 cc) using a doctor blade. The temperature of the slurry when applied was 15°C.
[0127] The resultant was then immersed in a coagulation solution containing water as a non-solvent, and then dried at 75° C. using an oven as a drying furnace to finally manufacture a separator for an electrochemical device. The results are shown in Table 3 below.
[0128] Examples B to D Fluorine-based binder polymer and polyvinyl acetate A separator was prepared in the same manner as in Example A, except that the weight ratio of the binder polymer was controlled as shown in Table 3 below.
[0129] Comparative examples A and B Fluorine-based binder polymer and polyvinyl acetate A separator was prepared in the same manner as in Example A, except that the weight ratio of the binder polymer was controlled as shown in Table 3 below.
[0130] [Table 3]
[0131] In Table 3, in the case of Comparative Example B, Ventilation time The increase rate of the electrode adhesive strength was not high compared to the increase rate of the electrode adhesive strength, so it was difficult to expect the effects of the present invention. On the other hand, in the case of Comparative Example A, the electrode adhesive strength did not reach the target value of the present invention.
[0132] [Experimental Example 4] Experimental Example 4 is polyvinyl acetate 1 shows examples and comparative examples in which other binder polymers are used instead of the binder polymer.
[0133] Example 1 The separation membrane was prepared in the same manner as in Example II, and the results are shown in Table 4.
[0134] Comparative Example 1 Polyvinyl acetate A separator was prepared in the same manner as in Example 1, except that a polymethyl methacrylate (PMMA) binder polymer was used instead of the binder polymer. The results are shown in Table 4.
[0135] Comparative Example 2 Polyvinyl acetate A separator was prepared in the same manner as in Example 1, except that a polyamide binder polymer was used instead of the binder polymer. The results are shown in Table 4.
[0136] Comparative Example 3 Polyvinyl acetate A separator was prepared in the same manner as in Example 1, except that a polyacrylate binder polymer was used instead of the binder polymer. The results are shown in Table 4.
[0137] [Table 4]
[0138] As can be seen from Table 4, polyvinyl acetate When a polyamide, polymethyl methacrylate, or polyacrylate binder polymer was used instead of the binder polymer, it was difficult to simultaneously satisfy the degree of blocking of the porous polymer substrate, the thermal shrinkage rate, and the adhesive strength with the electrode.
[0139] Evaluation method 1) Measurement of the degree of pore blockage in porous polymer substrates The porous coating layer in the separator was removed with cellophane tape (3M cat. 810D) two or three times, and then punched out to a diameter of 19π. The punched separator was placed in a CR2610 coin cell and filled with an electrolyte of ethylene carbonate / propylene carbonate / diethyl carbonate (EC / PC / DEC = 30:20:50 (wt%)) in which 1M lithium hexafluorophosphate (LiPF6) was dissolved to fabricate a coin cell. The AC resistance of the fabricated coin cell was measured, and the results are shown in Table 1. The AC resistance was measured at 1KHz using EIS (manufactured by Ametech Co., Ltd.) and was shown as the average value of five measurements.
[0140] 2) Measurement of heat shrinkage rate The heat shrinkage rate was calculated by (initial length-length after heat shrinkage treatment at 150°C for 30 minutes) / (initial length)×100.
[0141] 3) Measurement of adhesion strength between electrode and separator To measure the adhesive strength (Lami strength) between the electrode and the separator, a negative electrode was prepared as follows.
[0142] First, artificial graphite, carbon black, carboxymethyl cellulose (CMC), and styrene butadiene rubber (SBR) were mixed with water in a weight ratio of 96:1:2:2 to prepare a negative electrode slurry. 2 The resulting mixture was coated on copper foil to form a thin electrode plate, which was then dried at 135°C for more than 3 hours and pressed to prepare a negative electrode.
[0143] The manufactured negative electrode was cut to a size of 25 mm x 100 mm and prepared. The separator manufactured in the examples and comparative examples was cut to a size of 25 mm x 100 mm and prepared. The prepared separator and negative electrode were stacked, sandwiched between 100 μm PET films, and bonded using a flat press. At this time, the flat press was performed by heating and pressing at 60 ° C and a pressure of 6.5 MPa for 1 second. The bonded separator and negative electrode were attached to a slide glass using double-sided tape. The end of the separator adhesive surface (10 mm or less from the end of the adhesive surface) was pulled away, and the separator was attached to a 25 mm x 100 mm PET film and a single-sided adhesive tape so that the longitudinal direction was connected. Then, the slide glass was attached to the lower holder of a UTM device (LFPlus manufactured by LLOYD Instruments), and the separator and the attached PET film were attached to the upper holder of the UTM device. A force was applied at a measurement speed of 300 mm / min and 180° to measure the force required to peel the negative electrode from the porous coating layer facing the negative electrode.
Claims
1. A porous polymer substrate; a porous coating layer formed on at least one surface of the porous polymer substrate, the porous coating layer including inorganic particles, a fluorine-based binder polymer, and a polyvinyl acetate binder polymer; the porous coating layer has a structure in which the inorganic particles are dispersed in a matrix formed by the fluorine-based binder polymer and the polyvinyl acetate binder polymer, and the fluorine-based binder polymer, the polyvinyl acetate binder polymer, and the inorganic particles are uniformly distributed in a thickness direction of the porous coating layer; The content of the inorganic particles is 70 parts by weight or more based on 100 parts by weight of the porous coating layer, The content of the polyvinyl acetate binder polymer is 30 parts by weight or more and less than 80 parts by weight based on 100 parts by weight of the total content of the binder polymer, The weight average molecular weight of the fluorine-based binder polymer is 100,000 to 800,000; The polyvinyl acetate binder polymer has a weight average molecular weight of 200,000 to 1,000,000.
2. 2. The separator for a lithium secondary battery according to claim 1, wherein the content of the polyvinyl acetate binder polymer is 30 to 75 parts by weight based on 100 parts by weight of the binder polymer.
3. 3. The separator for a lithium secondary battery according to claim 1, wherein the separator has an adhesive strength with an electrode of 60 gf / 25 mm or more.
4. The separator for a lithium secondary battery according to claim 1 , wherein the separator has a thermal shrinkage of 10% or less in at least one of a machine direction and a transverse direction measured after heating at 150° C. for 30 minutes.
5. The battery includes a positive electrode, a negative electrode, and a separator interposed between the negative electrode and the positive electrode, An electrochemical element, wherein the separation membrane is the separation membrane according to claim 1 .
6. The electrochemical device according to claim 5 , which is a lithium secondary battery.
Citation Information
Patent Citations
Method for producing nanophase separated structure by polymer blend
JP2008266469A
Separator for nonaqueous secondary battery, and nonaqueous secondary battery
JP2018163872A
Layered body, separator, and non-aqueous secondary battery
WO2016031466A1
Non-aqueous secondary battery separator and non-aqueous secondary battery
WO2018055882A1
Separator and electrochemical device comprising same
WO2020060310A1